PENGARUH PEMAHAMAN PERATURAN PAJAK, PENERAPAN KEBIJAKAN PAJAK, DAN KEMUDAHAN ADMINISTRASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK HOTEL DAN RESTORAN DI KABUPATEN GIANYAR - Ni Nyoman Suarcini; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2022)
Regional Revenue Service Gianyar Regency has tried to improve taxpayer compliance in its work environment, but it is still not running effectively considering the various factors that influence it. The goal to be achieved is to find out whether you understand the regulations on taxation, the tax policies applied, and the administration that makes it easy to give an influence on the compliance of hotel and restaurant taxpayers in Gianyar Regency to pay taxes. The population in this study were hotel and restaurant taxpayers in Gianyar Regency, with the method of determining the sample using the Slovin formula, 94 taxpayers were used as samples by sampling using proportional stratified random sampling. Multiple linear regression was used as the analytical method, assisted by the SPSS 23.0 for Windows program. This study shows the results that understanding tax regulations, applied tax policies, and easy administration can increase the compliance of hotel and restaurant taxpayers in Gianyar Regency to pay taxes.